EFFECTIVENESS OF CONTROL AND REPRESSION CAMPAIGNS ON RTA MORTALITY IN A LOW INCOME COUNTRY. (7th October 2012) - Sobngwi, J; Taniform, P; Lagarde, E
Abstract : Background: On the occasion of the launch of the road safety decade, Cameroon government has conducted a prevention campaign with control and punishment of speeding, and alcohol consumption by drivers on the main intercity roads of Cameroon in June 2011. Objectives: We sought to evaluate the impact of control and punishment campaigns conducted in Cameroon in 2011 on road traffic accident (RTA) numbers and fatality rate. Methods: We used the computerised database of RTAs in Cameroon, and compared the period preceding the prevention campaign (January–May 2011) to the period of the prevention campaigns (June–December 2011). Results: Overall 1425 crashes and 1445 death were recorded in 2011, indicating a 47% decrease of RTAs and 9.7% decrease of death compared to 2010. The average number of RTA per month varied significantly form 128 before the campaign to 112 during the intervention (12% decrease). Overall in 2011, there were 101 deaths per 100 injury accident. The average monthly death rate was 136/month before and 109 during the intervention equivalent to 20% reduction in mortality rate. In addition the severity of injury accidents also decreased from 106 deaths per 100 injury accidents before to 98 during the intervention. Significance: The present results provide evidence of a significant reduction in the number of accidents and deaths by RTA in Cameroon obtained through a control-punishment campaign focusing on speed and alcohol consumption. The positive results concerned mainly the less fatal accidents, indicating the need for combined intervention that would also address road infrastructure and vehicles in order to further decrease mortality.